LEGAL ANALYSIS OF THE RESPONSIBILITY OF ONLINE TRANSPORTATION SERVICE PROVIDERS IN PROTECTING CONSUMERS WHO EXPERIENCE ACCIDENTS - Joan Yaspedo Purba; Andika Wijaya, Hilyatul Asfia; Hilyatul Asfia; Joanita Jalianery (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Online transportation services in Indonesia offer access to very easy transportation features, this poses a significant risk that worsens the guarantee of consumer protection. Even though the standards that must be achieved through a second analysis of three reasons: feasibility, governance, and the principle of accountability, if a violation occurs, what should consumers do. Through careful analysis, a dissection of the rules can be carried out because strict responsibility in Law Number 8 of 1999 concerning Consumer Protection provides a general legal umbrella in Article 4 paragraph (1) which states that consumers have the right to comfort, security, and safety when using goods and/or services. However, the law has not specifically regulated the legal relationship between application providers, drivers, and consumers in the context of online services.